Propofol Upregulates MicroRNA-30b to Inhibit Excessive Autophagy and Apoptosis and Attenuates Ischemia/Reperfusion Injury In Vitro and in Patients. (30th March 2022) - Lu, Zhiqi; Shen, Jiaojiao; Chen, Xubin; Ruan, Zhihua; Cai, Weihua; Cai, Shuyun; Li, Minjun; Yang, Yihui; Mo, Jian; Mo, Guixi; Lu, Yan; Tang, Jing; et al.
Abstract : Evidence reveals that propofol protects cells via suppressing excessive autophagy induced by hypoxia/reoxygenation (H/R). Previously, we found in a genome-wide microRNA profile analysis that several autophagy-related microRNAs were significantly altered during the process of H/R in the presence or absence of propofol posthypoxia treatment (P-PostH), but how these microRNAs work in P-PostH is still largely unknown. Here, we found that one of these microRNAs, microRNA-30b (miR-30b), in human umbilical vein endothelial cells (HUVECs) was downregulated by H/R treatment but significantly upregulated by 100 M propofol after H/R treatment. miR-30b showed similar changes in open heart surgery patients. By dual-luciferase assay, we found that Beclin-1 is the direct target of miR-30b. This conclusion was also supported by knockdown or overexpression of miR-30b. Further studies showed that miR-30b inhibited H/R-induced autophagy activation. Overexpression or knockdown of miR-30b regulated autophagy-related protein gene expression in vitro. To clarify the specific role of propofol in the inhibition of autophagy and distinguish the induction of autophagy from the damage of autophagy flux, we used bafilomycin A1. LC3-II levels were decreased in the group treated with propofol combined with bafilomycin A1 compared with the group treated with bafilomycin A1 alone after hypoxia and reoxygenation. Moreover, HUVECs transfected with Ad-mCherry-GFP-LC3b confirmed the inhibitory effect of miR-30b on autophagy flux. Finally, we found that miR-30b is able to increase the cellular viability under the H/R condition, partially mimicking the protective effect of propofol which suppressed autophagy via enhancing miR-30b and targeting Beclin-1. Therefore, we concluded that propofol upregulates miR-30b to repress excessive autophagy via targeting Beclin-1 under H/R condition. Thus, our results revealed a novel mechanism of the protective role of propofol during anesthesia. Clinical Trial Registration Number . This trial is registered with ChiCTR-IPR-14005470 . The name of the trial register: Propofol Upregulates MicroRNA-30b to Repress Beclin-1 and Inhibits Excessive Autophagy and Apoptosis.